PENYULUHAN PENINGKATAN PENGETAHUAN MASYARAKAT TERHADAP HIPERTENSI - Iin Ernawati; Safira Yulita (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Hypertension is one of the main causes of complications of cardiovascular disease. The success of therapy is influenced by adherence to hypertension therapy. Knowledge related to hypertension includes the definition of hypertension, medication, food that can be consumed, and medication adherence with taking medication, which are the main and important things in controlling blood pressure. Based on this background, community service was carried out related to counseling on increasing public knowledge about hypertension. This counseling is carried out online because it is related to Covid 19, which is carried out on students and some of the general public. After statistical analysis, online counseling related to hypertension knowledge can increase knowledge which is measured using the HKLS (Hypertension Knowledge Level Scale) questionnaire instrument, with P value < 0.05 (statistically significant). The hypertension knowledge score from the HKLS questionnaire increased after being given counseling.